SENSORY AND CHEMICAL PROPERTIES OF SHRIMP HEAD WASTE–BASED BIOFLAVOR: KARAKTERISTIK SENSORI DAN KIMIA BIOFLAVOR BERBASIS LIMBAH KEPALA UDANG - Sri Ayu Insani; Wahdania; Anhar Rozi; Uswatun Hasanah; Amarullah (PT. ROCE WISDOM ACEH, 2026)
Shrimp head waste is a byproduct of the fishing industry that could be used as a raw material for natural flavorings. This study aims to determine the yield, chemical characteristics, and sensory acceptance of bioflavor powder derived from shrimp head waste as an alternative to MSG. The bioflavor production process includes drying, grinding, and sieving. Parameters analyzed include yield, moisture content, ash content, protein content, and organoleptic tests (color, aroma, texture, and appearance). The results of the study indicate that shrimp head bioflavor powder yields 47.7%, with a moisture content of 3.7%, an ash content of 29.84%, and a protein content of 50.93%, which meet the quality requirements of SNI fishmeal. The organoleptic test showed an average hedonic value of 8.24, placing it in the highly liked category for panelists. Based on these results, shrimp head waste-based bioflavor powder has good chemical and sensory qualities and shows potential as a natural food additive to replace MSG, making it nutritious and environmentally friendly.